Regenstrief teaching electronic medical record (tEMR) platform: a novel tool for teaching and evaluating applied health information technology. Issue 1 (17th March 2021) - Takesue, Blaine Y; Tierney, William M; Embi, Peter J; Mamlin, Burke W; Warvel, Jeff; Litzelman, Debra K
Abstract: The objective of this study is to provide an overview of the Regenstrief Teaching Electronic Medical Record (tEMR), how the tEMR could be used, and how it is currently being used in health professions education. The tEMR is a derivative of a real-world electronic health record (EHR), a large, pseudonymized patient database, and a population health tool designed to support curricular goals. The tEMR has been successfully adopted at 12 health professional, public health, and health information technology (HIT) schools, with over 11 800 unique student users and more than 74 000 logins, for case presentation, to develop diagnostic and therapeutic plans, and to practice documentation skills. With the exponential growth of health-related data and the impact of HIT on work-life balance, it is critical for students to get early EHR skills practice and understand how EHR's work. The tEMR is a promising, scalable, flexible application to help health professional students learn about common HIT tools and issues.